Manejo de los recursos naturales y el bienestar familiar en tres comunidades en el área de conservación regional comunal Tamshiyacu Tahuayo, Loreto, 2021 - Goncálvez Arévalo, Myshellth Bonney (2022)
The present study seeks to know the benefits obtained by these populations from the establishment of the Tamshiyacu-Tahuayo Regional Communal Conservation Area (ACR CTT), for this we worked with three communities located in the buffer zone of the ACR CTT, applying semi-structured surveys to 48 heads of households, 3 communal authorities, 3 coordinators of local monitoring organizations and 3 existing management groups, which allowed to collect information on the management of natural resources and family well-being of three communities. From the evaluations carried out, all families make use of natural resources within the RTA and in the communal territories, where the main resources used were, game animals, fish for consumption, among others. Families also diversify their economic activities, with fishing (93,75%) and agriculture (85,42%) as the most important. Finally, 89,58% of the families evaluated affirm that the establishment of the ACR has contributed to the well-being of the communities, being food (85,42%), technical knowledge (70,83%), community organization (56,25%), housing infrastructure and basic services (39.59%), the aspects that are perceived to improve the most. The management of natural resources has a positive impact on the family well-being of three communities settled in the buffer zone of the Tamshiyacu Tahuayo Regional Community Conservation Area.